2017
DOI: 10.1590/1984-0462/;2017;35;1;00012
|View full text |Cite
|
Sign up to set email alerts
|

Atividade Física E Gordura Corporal De Adolescentes Vivendo Com Hiv: Um Estudo Comparativo

Abstract: Objective: To compare regular physical activity among adolescents living with human immunodeficiency virus (HIV) with their healthy peers, and to evaluate the relationship with anthropometric indicators of body fat. Methods: This was a cross-sectional study which investigated two groups: 57 adolescents (10-15 years of age) living with HIV, and 54 apparently healthy adolescents matched for sex and age. Physical activity was evaluated using a questionnaire and anthropometric measurements were performed. The grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…When looking specifically at children with HIV, the majority of children preferred low-impact exercise such as soccer and walking in boys and jogging and walking in girls [24]. When further analyzing the data, the study found that the pediatric participants did not partake in activity over the weekends and most of the activity was completed in physical education classes throughout the week at school [24]. Group-prescribed exercise can potentially be beneficial in children as opposed to individual exercise routines.…”
Section: Physical Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…When looking specifically at children with HIV, the majority of children preferred low-impact exercise such as soccer and walking in boys and jogging and walking in girls [24]. When further analyzing the data, the study found that the pediatric participants did not partake in activity over the weekends and most of the activity was completed in physical education classes throughout the week at school [24]. Group-prescribed exercise can potentially be beneficial in children as opposed to individual exercise routines.…”
Section: Physical Activitymentioning
confidence: 98%
“…In general, the HIV population has been found to have not only lower self-reported activity levels, but those who did report were more likely to mention light activity levels [13]. When looking specifically at children with HIV, the majority of children preferred low-impact exercise such as soccer and walking in boys and jogging and walking in girls [24]. When further analyzing the data, the study found that the pediatric participants did not partake in activity over the weekends and most of the activity was completed in physical education classes throughout the week at school [24].…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is relevant to mention that these changes may favor a decrease in health-related physical aptitudes and increase the risk of developing cardiovascular diseases in children and adolescents living with HIV compared to the uninfected population in the same age group [ 6 , 10 , 11 , 12 , 13 ]. In the literature, the importance and benefits of physical activity for the health of this population are well established; however, the physical fitness of adolescents living with HIV needs to be discussed more [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with HIV are reported to have lower overall scores for habitual physical activity, with shorter times for physical activity after school. Reinforcing these issues, children and adolescents living with chronic conditions other than HIV also have restrictions and inadequate levels of physical activity and sports practice, all of which predispose the individual to negative health factors and low physical fitness due to the sedentary lifestyle adopted because of various conditioning factors [ 11 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%